Jesus : A Prophet of Islam - Ata ur-Rahim, Muhammad (Karachi, Pakistan Begum Aisha Bawany Waqf, 1979)
First published in 1977, Muhammad 'Ata ur-Rahim's classic text examines Jesus as a prophet teaching the Unity of God, and the historical collapse of Christianity as it abandoned his teaching. Now revised by coauthor Ahmad Thomson, the book sketches the dramatic picture of the original followers of Jesus who affirmed Unity, showing how Christianity became the fiction that replaced their truth. A wide-ranging study that covers the Gospel of Barnabas, the Gospel of Hermes, the shepherd, early and later Unitarian Christians, and Jesus in the gospels and in the Qur'an and hadith, Jesus: Prophet of Islam argues persuasively that the idea of Jesus as part of a trinity was a Greek pagan concept adopted by early Christian missionaries to gain converts among the Greeks, and did not become a widely accepted Christian doctrine until after the Council of Nicea in 325 A.D.
Include Notes
Keywords: Islamic interpretations of Jesus Christ -- Jesus Christ -- Unitarianism -- Interfaith relations